Restoration of mangrove co-management to sequester coastal blue carbon - Adenan, Rudianto (Advances in Social Sciences Research Journal, 2018)
Destruction of mangrove forests has become a major concern in Indonesia due to issues such as cutting for timber, fuel and charcoal. Mangroves are cleared for timber, charcoal and firewood. Because of higher calorific value, the mangrove twigs are used as firewood. To investigate whether mangrove restoration can absorb carbon and store it in the soil by using co-management approach, it is necessary to take the research sample in Jenu area, Tuban Regency, East Java Province, Indonesia. The condition of mangrove forest in coast of Jenu indicates the heavy degraded of mangrove forests. The purpose of this study, firstly, is building co-management model among stakeholders involved. Secondly, to describe the model of co management to restore mangrove forests to increase sequestering in coast of Jenu. The methodology used to achieve the research objective is using Generalized Structured Component Analysis (GSCA). GSCA offers a global least squares optimization criterion. The result of this study shows local government, community, and the private sector are working together to serve the public in an ethical and open manner that engenders accountability. Beside, the translation of co-management is based on 7(seven) elements. they are a) equality in deliberation; (b) public policy formulation as agreement between community, government and private sector; (c) transparency and open management among three parties involved; (d) recognition and achievement awards to community groups that support restoration activities; (e) law enforcement on violators; (f). monitoring the effectiveness of ecosystem restoration activities; (g) facilitation of intercommunity conflict.